Intelligent elderly care I - Loh, Chao Hong. (2013)
This Final Year Project is about a GPS locator that design for dementia people to have more freedom and also to lesser the burden of the care giver. The main components using for this prototype is using a GPS module, a GPS Shield, a Cellular Shield, and a Arduino Uno (microcontroller). With the use of online server, care givers are allow to track the location of the patients if they are away of house. The information of location of the patients will update to the server continuously in order to give real time positioning information to care givers. Throughout the this project, I had learnt how to do planning for a project, learnt to programming in C++, MySQL database and gain more experience in using Arduino. This prototype currently is available to retrieve the altitude data by using the GPS module with GPS shield; SQL database created and ready to store the altitude data from server; Cellular shield able to connect to the network and connect to the server.